Managing agricultural price volatility in Africa. Context matters for policy effectiveness - Maître d’Hôtel, Elodie; Alpha, Arlène; Beaujeu, Raphaël; Gérard, Françoise; Levard, Laurent (Perspective, 2011)
<span style="font-size: 10pt; font-family: Arial; font-style: normal;" data-sheets-value="{"1":2,"2":"Soaring agricultural prices in 2007/2008, followed by decreasing prices in 2009/2010 then a new surge in late 2010/ 2011, have placed the management of agricultural price volatility at the heart of policy debates. Many developing countries have implemented policies to limit agricultural price volatility and its adverse effects, without always achieving the expected results. Analysis of recent experiences in Africa shows that in order to be effective, a policy measure must meet four conditions: it must be based on robust knowledge; it must be predictable; its funding must be secured; and its enforcement must be monitored."}" data-sheets-userformat="{"2":585,"3":[null,0],"6":{"1":[{"1":2,"2":0,"5":[null,2,0]},{"1":0,"2":0,"3":3},{"1":1,"2":0,"4":1}]},"9":0,"12":0}">Version française de l'article <span style="font-size: 10pt; font-family: Arial; font-style: normal;" data-sheets-value="{"1":2,"2":"Soaring agricultural prices in 2007/2008, followed by decreasing prices in 2009/2010 then a new surge in late 2010/ 2011, have placed the management of agricultural price volatility at the heart of policy debates. Many developing countries have implemented policies to limit agricultural price volatility and its adverse effects, without always achieving the expected results. Analysis of recent experiences in Africa shows that in order to be effective, a policy measure must meet four conditions: it must be based on robust knowledge; it must be predictable; its funding must be secured; and its enforcement must be monitored."}" data-sheets-userformat="{"2":585,"3":[null,0],"6":{"1":[{"1":2,"2":0,"5":[null,2,0]},{"1":0,"2":0,"3":3},{"1":1,"2":0,"4":1}]},"9":0,"12":0}">Soaring agricultural prices in 2007/2008, followed by decreasing prices in 2009/2010 then a new surge in late 2010/ 2011, have placed the management of agricultural price volatility at the heart of policy debates. Many developing countries have implemented policies to limit agricultural price volatility and its adverse effects, without always achieving the expected results. Analysis of recent experiences in Africa shows that in order to be effective, a policy measure must meet four conditions: it must be based on robust knowledge; it must be predictable; its funding must be secured; and its enforcement must be monitored.